An Exploration of Self-Directed Learning in Numerical Mathematics - Muhammad Istiqlal; Wulan Izzatul Himmah (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2019)
The present study aims to describe the students’ self-directed learning in numerical mathematics. It also explores the weakness of their self-directed learning based on four determined indicators. One out of four indicators will be prioritized for optimization. Grounded in a quantitative descriptive research, a survey was used to collect the data. 56 third-year students taking numerical methods course were recruited to participate. Population technique was employed to establish the research sample. The findings expose that the students’ self-directed learning in numerical mathematics was relatively low. The obtained data illustrated that 54% of participants showed low self-directed learning, 45% of them demonstrated moderate self-directed learning, and 2% of the research respondents were noticed to possess high self-directed learning in numerical mathematics. The indicators that received a priority scale for special treatment were the fourth indicator with the value level of 52%, the third indicator of 58%, the second indicator of 63%, and the first indicator of 75% respectively. This study recommends further researchers to escalate students’ self-directed learning in numerical mathematics by prioritizing the fourth and third indicators, namely: performing self-confidence, doing assignments independently, and taking decisions and initiatives to deal with experienced problems.